Current challenges in laboratory diagnostics of autonomous cortisol secretion in adrenal incidentalomas : Diagnosis of autonomous cortisol secretion - Antonić, Tamara; Petrović Mucok, Ana; Stefanović, Aleksandra (Archives of Pharmacy, 2022)
Adrenal incidentalomas are unexpectedly identified adrenal masses without prior suspicion of the existence of adrenal disease. The majority of adrenal incidentalomas are benign adrenal adenomas (80–90%), and they are non-functioning adrenocortical adenomas in more than 70% of cases. Mild hypercortisolemia is the most common finding in hormonally active adrenal incidentalomas. It is defined as autonomous cortisol secretion in up to 15% of patients. Despite a lot of research that anticipated higher cardiometabolic risk in patients with autonomous cortisol secretion, there is still no clear consensus on biochemical criteria for an autonomous cortisol secretion diagnosis in patients with adrenal incidentalomas. This review delineates the advantages and limitations of different laboratory tests recommended for the diagnosis of autonomous cortisol secretion in adrenal incidentalomas.